Reciprocal Duties of the Business Executive and the Government - Albregts, Auguste (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1957)
SummaryThe following article is an attempt by its Author to answer the following question: What are the reciprocal duties of the business executive and the State? After defining the State and pointing to the limits of State intervention, Professor Albregts indicates how government has been called to act more and more on the economic process, and what such a trend means to the business executive. He finally puts forward as a solution the "organic conception" of economic organization based on the Christian social doctrine.